SMartyPerspective: a perspective-based inspection technique for software product lines - Bettin, Giovanna; OliveiraJr, Edson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Software Product Line (SPL) is an approach for reusing software artifacts for a specific domain. To improve products quality, verification and validation activities for SPL artifacts are necessary, thus defects are not propagated to derived products. The lack of techniques to exploit the inherited SPL reuse characteristics, mainly in early phases, provides an opportunity to investigate how to improve SPL quality. Perspective-Based Reading (PBR) has proven to be a feasible inspection technique, as it considers different scenarios and perspectives of reviewers of software artifacts. Therefore, in this paper, we specify and evaluate SMartyPerspective, a PBR technique to inspect UML-based SPL diagrams (use case, class, sequence, and component) and feature diagrams. SMartyPerspective comprises Domain Engineering perspectives: Product Manager, Domain Requirements Engineer, Domain Architect, Domain Developer, and Domain Asset Manager. We evaluated it by carrying out a TAM-based qualitative study with 19 participants with experience in SPL and software inspections. We also used coding to analyze the open questions. Obtained results provide initial evidence SMartyPerspective is feasible for inspecting its supported diagrams.